2023
DOI: 10.1039/d2sm01478e
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the crystal and solution structure of a series of lipid-inspired ionic liquids

Abstract: The solid and solution-state structures of a series of lipid-inspired ionic liquids are correlated. X-ray crystallography is combined with UV-vis spectroscopy to gain a deep understanding of the interactions present in both phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Thus, with the butyl derivatives, an approximately equal percentage of reported structures are hydrates. However, as we previously observed, 41 moving to longer alkyl chains (C n , n ≥ 10) we see ca. 25% of reported structures as hydrates for C n -Mim (21 out of 85 total) and no reported hydrates for C n -Dimes (9 total).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, with the butyl derivatives, an approximately equal percentage of reported structures are hydrates. However, as we previously observed, 41 moving to longer alkyl chains (C n , n ≥ 10) we see ca. 25% of reported structures as hydrates for C n -Mim (21 out of 85 total) and no reported hydrates for C n -Dimes (9 total).…”
Section: Resultssupporting
confidence: 83%
“…This is in line with our previous studies wherein we observed similar trends. 41 The nature of this disparity, however, is still something which needs further study. In general, however, Dime-based ILs are less frequently found to crystallize as hydrates based on current data.…”
Section: Discussionmentioning
confidence: 99%
“…This is essential for the proper functioning of a cell and promotes intercellular signaling and metabolite transport. 11,12 In recent years, there have been a number of studies reported on the statistical mechanics of passive agents in active bath [13][14][15][16][17][18][19][20][21][22][23][24][25][29][30][31] and active agents in the passive bath. [26][27][28] Example includes a passive linear semiflexible polymer submerged in a bath of ABPs showing a wide range of transient states in 2D.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging this property, three crystals of the [C 16 dmim] cation were grown with a Br − , I − , and NTf 2 − anion. 79 It should be noted that the Cl − bearing compound was crystalline, although single crystals suitable for diffraction could not be isolated. The three crystals provided a wealth of knowledge concerning the structure of the cation, the non-covalent interactions present, and how the varying anions affect these interactions.…”
Section: Crystallographic Studies Of Lipid-like Ilsmentioning
confidence: 99%